(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we will deal about the importance of the study of the subject Fluid Dynamics in Engineering field. Students are more likely to study Engineering courses in the recent days. Engineering deals with the basic concepts of Mathematics, Physics and Chemistry. Though, Computer Science subject is a pulse to Engineering, the subjects, Mathematics, Physics and Chemistry are heart beat to Engineering courses. In this study, we will discuss where and how Fluid Dynamics stands as a crown to Engineering Field.